Real-Life Impact of Enfortumab Vedotin or Chemotherapy in the Sequential Treatment of Advanced Urothelial Carcinoma: The ARON-2 Retrospective Experience - Rizzo, Mimma; Morelli, Franco; Ürün, Yüksel; Buti, Sebastiano; Park, Se Hoon; Bourlon, Maria T; Grande, Enrique; Massari, Francesco; Landmesser, Johannes; Poprach, Alexandr; Takeshita, Hideki; Roviello, Giandomenico; et al. (Cancer medicine, 2025)
BACKGROUND: Recently, a plethora of novel systemic agents have been incorporated into the therapeutic armamentarium of advanced urothelial carcinoma (aUC). The antibody-drug conjugate (ADC), enfortumab vedotin (EV), has demonstrated relevant clinical benefit in patients with aUC refractory to platinum and immune-checkpoint inhibitor (ICI) therapy. Our study provides a retrospective, international, real-world analysis comparing the effectiveness of EV to chemotherapy in this setting. METHODS: The data were extracted from the medical records of patients treated with EV or chemotherapy following pembrolizumab for recurrent or progressive aUC after platinum-based chemotherapy. Patients were assessed for overall survival (OS), progression-free survival (PFS), overall response rate (ORR) and duration of response (DoR). RESULTS: Our analysis included 247 patients treated with EV (88, 36%) or chemotherapy (159, 64%). Median OS was 9.1 months (95%CI 7.2-10.7) in the overall study population, 13.6 months (95%CI 10.0-31.0) in patients receiving EV and 6.8 months (95%CI 6.0-8.9) in patients receiving chemotherapy (p < 0.001). The OS benefit of EV was not affected by primary tumour site and histology, metastatic sites, type of first platinum-based chemotherapy or response to pembrolizumab. In the EV cohort, the median PFS was significantly longer (8.8 months [95%CI 6.5-17.0] vs. 3.0 months [95%CI 2.6-3.7]) and the ORR was significantly higher (56% vs. 23%) than in the chemotherapy cohort. CONCLUSIONS: The results of our international analysis of real-world data confirm the effectiveness of EV in the sequential strategy of aUC patients who have received prior platinum-based chemotherapy and anti-PD-1 pembrolizumab, regardless of commonly considered prognostic factors. TRIAL REGISTRATION: ClinicalTrials.gov identifier: NCT05290038.
Keywords: pembrolizumab; Humans; lidé středního věku; enfortumab vedotin; karcinom z přechodných buněk; NCT05290038; urologické nádory; Female; Aged; Antibodies, Monoclonal; dospělí; protokoly protinádorové kombinované chemoterapie; výsledek terapie; ARON‐2 study; senioři; lidé; humanizované monoklonální protilátky; doba přežití bez progrese choroby; urothelial carcinoma; sequencing; Urologic Neoplasms; Adult; Antibodies, Monoclonal, Humanized; ženské pohlaví; imunokonjugáty; Male; nádory močového měchýře; Middle Aged; Retrospective Studies; Treatment Outcome; Antineoplastic Combined Chemotherapy Protocols; Carcinoma, Transitional Cell; Aged, 80 and over; monoklonální protilátky; Immunoconjugates; chemotherapy; real‐world data; senioři nad 80 let; Progression-Free Survival; retrospektivní studie; mužské pohlaví; Urinary Bladder Neoplasms